Child Marriage in Indonesia: Are Parents’ Protection and Responsibilities Involved? - Muniri, Akh Syamsul; Hadi, Abdul; Ghofur, Abdul (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2023)
A girl having a loved one to get married with is every parent’s happiness, contrary to the fact that underage marriage will not settle the issue where children are not prepared yet to deal with life problems and households. Departing from this issue, this research seeks to answer whether parents’ protection and responsibilities are involved in child marriage in the District of Pohjentrek, Pasuruan. This research is a field study in the District of Pohjentrek of Pasuruan, employing a qualitative method and a phenomenological approach. Research participants involved parents with their underage married children in 2020. Data were garnered from observation and in-depth interviews. The research results show that the involvement of parents represents the protection and responsibilities, ensuring affection and proper responsibilities given by the family or a spouse for a happier and everlasting marriage.